Arabic Language Learning Difficulties in Indonesian Islamic Schools: Linguistic and Non-Linguistic Perspectives - Diana Putri Oktavian; Saefullah Azhari; Nurul Istiqomah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study examines the problems of Arabic language learning encountered by eighth-grade students at MTs Taswirul Afkar Surabaya and explores teachers’ efforts to address these challenges. Arabic plays a crucial role in Islamic education; however, its learning process in non-native contexts often faces complex obstacles. This research employs a descriptive qualitative approach, with data collected through classroom observations, semi-structured interviews with teachers and students, and document analysis. The findings reveal that the problems of Arabic learning can be categorized into linguistic and non-linguistic aspects. Linguistically, students experience difficulties in mastering Arabic grammar (qawaid), developing speaking skills (kalam), and acquiring sufficient vocabulary (mufradat). Non-linguistic challenges include limited learning facilities, the predominance of conventional teaching methods, time constraints, and low learning motivation among some students. To overcome these issues, teachers implement several strategies, such as applying step-by-step grammar instruction, using language games (lu‘bah) to enhance speaking skills, assigning daily vocabulary memorization, and creatively utilizing simple and contextual learning media. The results indicate that these efforts contribute positively to increasing student engagement and improving learning outcomes. This study contributes theoretically to the development of Arabic language education by highlighting the interplay between linguistic and non-linguistic factors. Practically, it offers insights for teachers and policymakers to design more innovative, interactive, and motivational Arabic learning practices suited to the Indonesian madrasah context.